REALISM IN EDUCATION (Author: William Oliver Martin) - Ryan, William L. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1971)
William Oliver Martin. REALISM IN EDUCATION. New York: Harper and Row. 1969. 198 pp. 2.95.